THE EFFECT OF DIFFERENT SOIL TYPES AND SHADE LEVELS ON THE GROWTH OF Asystasia gangetica (L.) subsp. Micrantha ON THE SECOND CUTTING - W. W., Fuadah,; Witariadi, N. M.; Kusumawati, N. N. C. (Jurnal Peternakan Tropika, 2024)
A greenish-growth alternative to fodder could be made by planting land or shaded land. Research aims to identify the different types of soil and shade effects on the growth of Asystasia gangetica (L.) subsp. Micrantha on second cut. The study carried out in the Village of Sading, Mengwi District, Badung District, ran from April-June 2023. The design used is a complete random design (RAL) split splot by two factors. The main plot ( main plot ) is the land type: TM: Mediterranean Land; TL: Land of Latosol; And TR: Land of Regosol. Tenders ( sub plot ) are the swine shade: N1: 20%; N2: 40% shade; And N3:60% shade. From the treatment there are 9 combinations of treatment and three times of treatment that result in 27 experimental unit. The observed variable is: the height of the plant, the number of leaves, the number of branches, the diameter of the stem, the color of the leaf, and the area of the leaf. Studies suggest that there is no interaction of different types of soil and a different level of shade on the growth of Asystasia gangetica on a second cut. The treatment of soil types gives distinct results in high plant variables, the number of leaves and the extent of individual leaves per pot, is not real in the other, but rather in the regosol soils. The shade - level treatment of variable leaves per pot indicates distinct results are real but different is not real in other variables. The 40% degree of shade tends to bring out the best. It concludes that no interaction of soil type with a different degree of shade will affect the growth of Asystasia gangetica (L.) subsp. Micrantha on second cut. This type of land regosol (TR) produces Asystasia gangetica (L.) subsp. Micrantha tends best on second cuts. A 40% shade provides Asystasia gangetica (L.) subsp. Micrantha tends best on second cuts.